Hadith #567 - Sunan al-Nasa'i - Abu al-Aliyya al-Bara', Ziyad bin Feroz أبو العالية البراء زياد بن فيروز; Ahmed bin Manay' أحمد بن منيع; Hashaym bin Bashayr bin al-Qasim هشيم بن بشير بن القاسم; ibn Abbas; Mansur bin al-Ma'tamar al-Salmi منصور بن المعتمر بن عبد الله السلمي; Qatada قتادة (Sunan al-Nasa'i)
“I heard ‘Uqbah bin ‘Amir say: ‘There are three times during which the Messenger of Allah (ﷺ) forbade us from praying or burying our dead: When the sun had clearly started to rise until it was fully risen, when it was directly overhead at noon until it has passed the zenith, and when it was close to setting until it had fully set.'”
Grade:

Hadith #778 - Sunan al-Nasa'i - Abu al-Aliyya al-Bara', Ziyad bin Feroz أبو العالية البراء زياد بن فيروز; Ayoub al-Sakhtiyani أيوب السختياني; Ziyad bin Ayoub - Dulwiyya زياد بن أيوب بن زياد دلويه (Sunan al-Nasa'i)
It was narrated from Abdullah bin As Saib that the Messenger of Allah(ﷺ) prayed on the day of Conquest (of Makkah), and he put his sandals to his left.
Grade:

Hadith #859 - Sunan al-Nasa'i - Abdullah bin al-Samit عبد الله بن الصامت; Abu al-Aliyya al-Bara', Ziyad bin Feroz أبو العالية البراء زياد بن فيروز; Abu Dharr al-Ghaffari; Khalid bin al-Harith bin 'Ubaid خالد بن الحارث بن عبيد; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Muhammad bin Ibrahim bin al-Harith محمد بن إبراهيم بن الحارث; Shu'bah bin al-Hajjaj شعبة بن الحجاج (Sunan al-Nasa'i)
“What kept you from praying? Are you not a Muslim man?” He said: “Yes, but I had already prayed with my family.” The Messenger of Allah (ﷺ)said to him: “When you come you should pray with the people even if you have already prayed.”
Grade:

Hadith #1129 - Sunan al-Nasa'i - Abdul Wahab bin 'Abdul Majeed al-Thaqaf عبد الوهاب بن عبد المجيد الثقفي; Abu al-Aliyya al-Bara', Ziyad bin Feroz أبو العالية البراء زياد بن فيروز; Aisha bint Abi Bakr; Khalid bin Mahran al-Hadha' خالد بن مهران الحذاء; Muhammad bin Bashar Bindar محمد بن بشار بندار (Sunan al-Nasa'i)
The Prophet (ﷺ) used to say when prostrating: “Allahumma laka sajadtu wa laka aslamtu wa anta Rabbi, sajada wajhi lilladhi khalaqahu wa sawwarahu wa shaqqa sam’ahu wa basarahu, tabarak Allahu ahsanul-khaliqin ( O Allah, to You I have prostrated and in You I have believed and to You I have submitted, and You are my Lord. My face has prostrated to the One Who created it and formed it, and brought forth its hearing and sight. Blessed be Allah the best of Creators.)”
Grade:

Hadith #2870 - Sunan al-Nasa'i - Abu al-Aliyya al-Bara', Ziyad bin Feroz أبو العالية البراء زياد بن فيروز; Ayoub al-Sakhtiyani أيوب السختياني; Hiban bin Hilal حبان بن هلال; ibn Abbas; Muhammad bin Ma'mar bin Rabi' محمد بن معمر بن ربعي القيسي البحراني; Wahayb bin Khalid bin 'Ajlan al-Bahli وهيب بن خالد بن عجلان الباهلي (Sunan al-Nasa'i)
the Prophet set out from Al-Jirranah at night as if he were an ingot of silver (i.e., in whiteness and purity) and perfomed Umrah, then he came back in the mooring as if he had stayed there overnight.
Grade:

Hadith #2871 - Sunan al-Nasa'i - Abu al-Aliyya al-Bara', Ziyad bin Feroz أبو العالية البراء زياد بن فيروز; Ayoub al-Sakhtiyani أيوب السختياني; ibn Abbas; Muhammad bin Bashar Bindar محمد بن بشار بندار; Shu'bah bin al-Hajjaj شعبة بن الحجاج; Yahya bin Kathir bin Darham يحيى بن كثير بن درهم العنبري (Sunan al-Nasa'i)
the Messenger of Allah entered Makkah from the upper valley which is in Al-Batha and he left from the lower valley.
Grade:

Hadith #3057 - Sunan al-Nasa'i - Abu al-Aliyya al-Bara', Ziyad bin Feroz أبو العالية البراء زياد بن فيروز; Awf bin Abi Jamila al-A'rabi عوف بن أبي جميلة الأعرابي; ibn Abbas; Y'aqub bin Ibrahim bin Kathir يعقوب بن إبراهيم بن كثير بن زيد الدورقي (Sunan al-Nasa'i)
“Usamah bin Zaid was asked – while I was sitting with him: ‘How did the Messenger of Allah travel during the Farewell Pilgrimage when he moved on?’ He said: ‘He rode at a moderate pace, and if he found some open space, he would gallop.'”
Grade:

Hadith #3059 - Sunan al-Nasa'i - Abu al-Aliyya al-Bara', Ziyad bin Feroz أبو العالية البراء زياد بن فيروز; Awf bin Abi Jamila al-A'rabi عوف بن أبي جميلة الأعرابي; ibn Abbas; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان (Sunan al-Nasa'i)
the Prophet hurried in the valley of Muhassir.
Grade:

Hadith #4667 - Sunan Abi Dawud - Abu al-Aliyya al-Bara', Ziyad bin Feroz أبو العالية البراء زياد بن فيروز; Hafs bin 'Umar bin al-Harith حفص بن عمر بن الحارث; ibn Abbas; Qatada قتادة; Shu'bah bin al-Hajjaj شعبة بن الحجاج (Sunan Abi Dawud)
In the event of the dissension among Muslims an emerging sect will emerge ; one of the two parties that is nearer to the truth will kill it.
Grade: Sahih

Hadith #4857 - Sunan Abi Dawud - Abdah bin Sulaiman al-Klabi عبدة بن سليمان الكلابي أبو محمد الكوفي; Abu al-Aliyya al-Bara', Ziyad bin Feroz أبو العالية البراء زياد بن فيروز; Abu Burzah al-Aslami; Abu Hashim al-Rmany أبو هاشم الرماني; Hjaj bin Dinar حجاج بن دينار; Muhammad bin Hatm bin Yonus محمد بن حاتم بن يونس; Uthman bin Muhammad (Sunan Abi Dawud)
There are some expressions which a man utters three times when he gets up from an assembly he will be forgiven for what happened in the assembly; and no one utters them in an assembly held for a noble cause or for remembrance of Allah but that is stamped with them just as a document is stamped with a signet-ring. These expressions are: Glory be to Thee, O Allah, and I begin with praise of Thee, there is no god but thou; I ask Thy pardon, and return to Thee in repentance.
Grade: Sahih

Hadith #4906 - Sunan Abi Dawud - Abu al-Aliyya al-Bara', Ziyad bin Feroz أبو العالية البراء زياد بن فيروز; ibn Abbas; Muslim bin Ibrahim al-Azdy مسلم بن إبراهيم الأزدي الفراهيدي; Qatada قتادة; Zayd bin Akhzm زيد بن أخزم; Zayd ibn Harithah (Sunan Abi Dawud)
The Prophet (ﷺ) said: Do not invoke Allah’s curse, Allah’s anger, or Hell.
Grade: Hasan

Hadith #77 - Jami' al-Tirmidhi - Abdul Salam bin Harb bin Salm al-Mala'i عبد السلام بن حرب بن سلم النهدي الملائي; Abu al-Aliyya al-Bara', Ziyad bin Feroz أبو العالية البراء زياد بن فيروز; Abu Khalid al-Dalani أبو خالد الدالاني الأسدي; ibn Abbas; Isma'il bin Musa al-Fazari al-Siddi إسماعيل بن موسى الفزاري السدي; Qatada قتادة (Jami' al-Tirmidhi)
he saw the Prophet sleeping, while in the prostration position, until he snored or snorted. Then he stoodup to pray. So I said: “O Messenger of Allah! You were sleeping?” He said: “Wudu is not required except for sleeping while reclining. For when one reclines, joints relax.”
Grade:

Hadith #183 - Jami' al-Tirmidhi - Abu al-Aliyya al-Bara', Ziyad bin Feroz أبو العالية البراء زياد بن فيروز; Ahmed bin Manay' أحمد بن منيع; Hashaym bin Bashayr bin al-Qasim هشيم بن بشير بن القاسم; ibn Abbas; Mansur bin al-Ma'tamar al-Salmi منصور بن المعتمر بن عبد الله السلمي; Qatada قتادة (Jami' al-Tirmidhi)
“I head more than one of the Companions of the Prophet; Umar bin Al-Khattab among, and he was one of the most beloved among them to me – (narrating) that Allah’s Messenger prohibited the Salat after Fajr until the sun had risen, and the Salat after Asr until the sun had set.”
Grade:

Hadith #580 - Jami' al-Tirmidhi - Abdul Wahab bin 'Abdul Majeed al-Thaqaf عبد الوهاب بن عبد المجيد الثقفي; Abu al-Aliyya al-Bara', Ziyad bin Feroz أبو العالية البراء زياد بن فيروز; Aisha bint Abi Bakr; Khalid bin Mahran al-Hadha' خالد بن مهران الحذاء; Muhammad bin Bashar Bindar محمد بن بشار بندار (Jami' al-Tirmidhi)
“When the Messenger of Allah would prostrate (for recitation of) the Qur’an, he would say: (Sajada wajhiya lilladhi khalaqahu wa shaqqa sam’ahu wa basarahu bihawlihi wa quwwatihi.) (I have prostrated my face to the One Who created it, and made its hearing and vision, though His ability and power.)”
Grade:

Hadith #1759 - Jami' al-Tirmidhi - Abdur Rahman bin Mahdi عبد الرحمن بن مهدي; Abu al-Aliyya al-Bara', Ziyad bin Feroz أبو العالية البراء زياد بن فيروز; Muhammad bin Hmyd bin Hyan محمد بن حميد بن حيان; Zayd bin al-Habab al-'Akli زيد بن الحباب أبو الحسين العكلي (Jami' al-Tirmidhi)
“Use Ithmid for it clears the vision and grows the hair (eye-lashes).”
Grade:

Hadith #2038 - Jami' al-Tirmidhi - Abu al-Aliyya al-Bara', Ziyad bin Feroz أبو العالية البراء زياد بن فيروز; ibn Abbas; Qatada قتادة; Zayd bin Akhzm زيد بن أخزم (Jami' al-Tirmidhi)
“Some Bedouins asked: ‘O Messenger of Allah (s.a.w) shall we treat (our ill)?’ He said: ‘Yes, O worshipers of Allah! Use remedies. For indeed Allah did not make a disease but He made a cure for it’ – or – ‘a remedy. Except for one disease.’ They said: ‘O Messenger of Allah (s.a.w)! What is it?’ He said: ‘Old age.'”
Grade:

Hadith #3337 - Jami' al-Tirmidhi - Abu al-Aliyya al-Bara', Ziyad bin Feroz أبو العالية البراء زياد بن فيروز; al-Fadl bin Musa al-Synany الفضل بن موسى السيناني; al-Husain bin Hryth الحسين بن حريث; al-Rabi' bin Anas al-Bakry الربيع بن أنس البكري; Isa bin 'Ubaid bin Malik عيسى بن عبيد بن مالك; Ubayy ibn Ka'b (Jami' al-Tirmidhi)
“I heard that the Messenger of Allah saying: ‘Whoever is interrogated during the reckoning, then he will ruined.’ I said: ‘O Messenger of Allah! Allah, Blessed is He and Most High, said: ‘As for him who will be given his record in his right hand…” up to His saying: ‘…an easy reckoning.’ He said: ‘That is (only) the presentation.’”
Grade:

Hadith #3451 - Jami' al-Tirmidhi - Abu al-Aliyya al-Bara', Ziyad bin Feroz أبو العالية البراء زياد بن فيروز; al-Walid bin Muslim al-Quraishi الوليد بن مسلم القرشي; Ali bin Hujr bin Iyas bin Maqatil علي بن حجر بن إياس بن مقاتل; Ubayy ibn Ka'b; Zuhayr bin Muhammad al-Tamimi زهير بن محمد التميمي (Jami' al-Tirmidhi)
that one of the two men cursed the other next to the Prophet (ﷺ), until anger could be recognized in the face of one of them. So the Prophet (ﷺ) said: “Verily, I know a statement, that if he were to say it, his anger would leave: ‘I seek refuge in Allah from Shaitan, the rejected (A`ūdhu billāhi minash-shaiṭānir-rajīm).’”
Grade:

Hadith #3605 - Jami' al-Tirmidhi - Abu al-Aliyya al-Bara', Ziyad bin Feroz أبو العالية البراء زياد بن فيروز; Abu Ja'far al-Razi أبو جعفر الرازي; Ahmed bin Manay' أحمد بن منيع; al-Rabi' bin Anas al-Bakry الربيع بن أنس البكري; Ubayy ibn Ka'b (Jami' al-Tirmidhi)
“There is a supplication that I memorized from the Messenger of Allah which I do not leave off: ‘O Allah, make me revere gratitude to You, make me increase in remembrance to You, make me follow Your advice, and (make me) guard over that which you have commanded (Allāhummaj`alnī u`aẓẓimu shuraka wa ukthiru dhikraka wa attabi`u naṣīḥataka wa aḥfaẓu waṣīyatak).’”This Hadith is Gharib
Grade:

Hadith #3606 - Jami' al-Tirmidhi - Abd bin Hameed bin Nasr عبد بن حميد بن نصر; Abu al-Aliyya al-Bara', Ziyad bin Feroz أبو العالية البراء زياد بن فيروز; Abu Ja'far al-Razi أبو جعفر الرازي; Ubaidullah bin Musa bin Abi al-Mukhtar عبيد الله بن موسى بن أبي المختار باذام (Jami' al-Tirmidhi)
“There is not a man who calls upon Allah with a supplication, except that he is answered. Either it shall be granted to him in the world, or reserved for him in the Hereafter, or, his sins shall be expiated for it according to the extent that he supplicated – as long as he does not supplicate for some sin, or for the severing of the ties of kinship, and he does not become hasty.” They said: “O Messenger of Allah, and how would he be hasty?” He (ﷺ) said: “He says: ‘I called upon m
Grade:

Hadith #1308 - Sunan Ibn Majah - Abu al-Aliyya al-Bara', Ziyad bin Feroz أبو العالية البراء زياد بن فيروز; Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Affan bin Muslim عفان بن مسلم بن عبد الله الصفار; Hmam bin Yahya bin Dinar همام بن يحيى بن دينار; ibn Abbas; Muhammad bin Bashar Bindar محمد بن بشار بندار; Muhammad bin Ja'far bin Abi Kathir محمد بن جعفر بن أبي كثير; Qatada قتادة; Shu'bah bin al-Hajjaj شعبة بن الحجاج (Sunan Ibn Majah)
“The Messenger of Allah (ﷺ) cursed women who visit graves.”
Grade:

Hadith #2920 - Sunan Ibn Majah - Abdur-Razzaq عبد الرزاق بن همام; Abu al-Aliyya al-Bara', Ziyad bin Feroz أبو العالية البراء زياد بن فيروز; ibn Abbas; Muhammad bin Yahya bin Hiban محمد بن يحيى بن حبان; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Sulaiman al-A'mash الأعمش / سليمان بن مهران (Sunan Ibn Majah)
“The Messenger of Allah (ﷺ) forbade tying up animals.”
Grade:

Hadith #3001 - Sunan Ibn Majah - Abu al-Aliyya al-Bara', Ziyad bin Feroz أبو العالية البراء زياد بن فيروز; Bakr bin Khlf al-Basri بكر بن خلف البصري; Da'ud bin Abi Hnd داود بن أبي هند; ibn Abbas; Muhammad bin Abi 'Adi محمد بن أبي عدي (Sunan Ibn Majah)
“I was a boy in the care of the Prophet (ﷺ) and my hand used to wander all over the plate. He said to me: ‘O boy! Say the Name of Allah, eat with your right hand, and eat from what is in front of you.’”
Grade:

Hadith #3142 - Sunan Ibn Majah - Abu al-Aliyya al-Bara', Ziyad bin Feroz أبو العالية البراء زياد بن فيروز; Ali bin Muhammad bin Ishaq al-Tanafasi علي بن محمد بن إسحاق الطنافسي; Awf bin Abi Jamila al-A'rabi عوف بن أبي جميلة الأعرابي; Hammad bin Usamah حماد بن أسامة - أبو أسامة; ibn Abbas (Sunan Ibn Majah)
“The Messenger of Allah (ﷺ) forbade making Nabidh in (earthenware) jars.”
Grade:

Hadith #3881 - Sunan Ibn Majah - Abu al-Aliyya al-Bara', Ziyad bin Feroz أبو العالية البراء زياد بن فيروز; Ali bin Muhammad bin Ishaq al-Tanafasi علي بن محمد بن إسحاق الطنافسي; ibn Abbas; Qatada قتادة; Waki' bin al-Jarrah وكيع بن الجراح (Sunan Ibn Majah)
“There would come a month when no smoke was seen in any of the households of the family of Muhammad (ﷺ). I said: “What did you eat?” She said: “The two black ones – dates and water.” But we had neighbors among the Ansar, sincere neighbors, who had domestic sheep, and they used to send some of their milk to us. (One of the narrators) Muhammad said: “And they were nine households.”
Grade: